TEACHER’S COMPETENCIES PROFILE IN DIGITAL TECHNOLOGY ERA: SPIRITUAL FORMATION AND BIBLICAL COMMUNITY - Chrismastianto, Imanuel Adhitya Wulanata; Wibawanta, Budi; Mumu, Billy; Sitepu, Debora Stefany; Milenia, Marisa (Universitas Pelita Harapan, 2022)
Christian education aims to bring students to have relationships and growth based on Christian Faith. For building this relationship and growing faith, teacher’s competencies are needed in implementing teaching and learning that is based on the Biblical Christian Worldview. During this digital technology era, Christian teachers are required to have competence for developing their Spiritual Formation and Biblical Community. This study aims to analyze the teacher's competencies to enhance spiritual formation and develop biblical community. The research was conducted by distributing a survey to 61 respondents at Christian private school Tangerang. Data from respondents was collected through an online questionnaire via Google form and analyzed data with descriptive qualitatively. The results on each aspect of Spiritual Formation (SF) and Biblical Community (BC) suggest that respondents have achieved an average score of 4.1 (good category) or has met the teacher competency profile criteria as expected. Nevertheless, there needs to be a relevant follow-up to improve teacher competence in the digital technology era in the aspect of Spiritual Formation and Biblical Community through professional development or similar training.Bahasa Indonesia Abstrak Natur pendidikan Kristen bertujuan untuk membawa peserta didik mengalami relasi dan pertumbuhan yang berlandaskan Iman Kristiani. Dalam membangun relasi dan pertumbuhan iman tersebut, dibutuhkan peran dan kompetensi guru Kristen dalam mengimplementasikan pengajaran yang sesuai dengan Biblical Christian Worldview (BCW). Pada era digital saat ini, guru Kristen dituntut untuk memiliki kompetensi dalam meningkatkan Spiritual Formation (pertumbuhan rohani peserta didik) dan Biblical Community (komunitas yang memiliki relasi dengan berwawasan Kristen Alkitabiah). Penelitian ini memiliki tujuan untuk menganalisis seberapa besar kompetensi guru dalam meningkatkan pertumbuhan rohani dan membangun komunitas yang berlandaskan prinsip Alkitabiah. Penelitian dilakukan dengan membagikan survei kepada guru di salah satu sekolah swasta Kristen Tangerang dengan responden sebanyak 61 orang. Data dari responden dikumpulkan melalui kuesioner online (google form) dan dianalisis secara deskriptif kualitatif. Hasil penelitian pada masing-masing aspek Spiritual Formation (SF) dan Biblical Community (BC), responden telah mencapai rata-rata angka 4,1 (kategori baik) atau telah memenuhi kriteria profil kompetensi guru sesuai yang diharapkan. Kendati demikian, perlu ada tindak lanjut yang relevan guna meningkatkan kompetensi guru di era digital dalam aspek Spritual Formation dan Biblical Community melalui pengembangan profesional ataupun pelatihan sejenis.